(untitled) (Theatrum historiae, 2013)
The aim of the study is to outline relations between midwives and men-obstetricians during the Early Modern Times. They experienced various situations in their status negotiations, various kinds of conflicts as well as times of cooperation and mutual tolerance. The study is based on sources from the German territory. In this territory the extensive production of original obstetrical work as well as the general acceptance and the translations of foreign, especially French writings can be discovered.